International Human Rights Law and Sexual Orientation - Wilets, James D. (1994)
Recently, the U.N. Human Rights Committee unanimously ruled that Tasmania had violated the International Covenant on Civil and Political Rights by criminalizing same-gender sexual activity. The Committee based its ruling on both privacy and equal protection grounds. This Article explores the interplay between international law and domestic laws of the world's nations regarding the fundamental human rights of sexual minorities. This Article analyzes this emerging legal and political dialectic by examining the domestic laws and constitutions of specific countries and the role of international and regional human rights systems in protecting the human rights of sexual minorities